DNA base-stacking assay utilizing catalytic hairpin assembly-induced gold nanoparticle aggregation for colorimetric protein sensing. Issue 22 (24th February 2016) - Chang, Chia-Chen; Chen, Chie-Pein; Chen, Chen-Yu; Lin, Chii-Wann
Abstract : A label-free and enzyme-free colorimetric sensing platform for the amplified detection of fibronectin was developed based on an ingenious combination of catalytic hairpin assembly and a base stacking hybridization-based gold nanoparticle aggregation strategy. Abstract : A label-free and enzyme-free colorimetric sensing platform for the amplified detection of fibronectin was developed based on an ingenious combination of catalytic hairpin assembly and a base stacking hybridization-based gold nanoparticle aggregation strategy. The detection limit of 2.3 pM is at least one order of magnitude lower than that of established fibronectin biosensors.